EXTREME INJURY. - Scarry, Elaine (Boston Review)
In this article the author discusses the threat of nuclear weapons in the U.S. She is critical of the president's power to order to launch nuclear weapons and the launch itself. She emphasizes that the dangers inherent in the redundancy, readiness and responsiveness of the stance of Americans on nuclear issues are further expanded through the mastery of hacking. She stresses the need for nation's citizens to rid the world of nuclear weapons and the extreme injuries they bring.